(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Lifelong education includes both formal and informal learning patterns across an individual’s life, aimed at continuous personal development and enhancing societal quality of life. This concept emerged as an extension of educational advancements, representing a broader, more profound understanding of learning that focuses on redesigning education to be more functional and impactful. In modern economies, lifelong education is increasingly recognised as a way to adapt to dynamic career paths and rapid technological changes. It is not only a tool for career advancement and employability but also a means to foster adaptability, creativity, and resilience. The focus on lifelong learning supports individuals in remaining competitive in evolving job markets, allowing them to expand their professional networks and achieve long-term success. As industries and the nature of work continue to evolve, lifelong learning is essential for maintaining relevance in an ever-changing landscape. Additionally, lifelong education has societal benefits, promoting social cohesion, civic engagement, and personal fulfilment. In the context of the digital economy, it provides individuals with the skills needed to thrive in a technology-driven environment, supporting both personal and professional growth.